2014
DOI: 10.1152/ajpregu.00522.2013
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myofiber VEGF is essential for the exercise training response in adult mice

Abstract: Vascular endothelial growth factor (VEGF) is exercise responsive, pro-angiogenic, and expressed in several muscle cell types. We hypothesized that in adult mice, VEGF generated within skeletal myofibers (and not other cells within muscle) is necessary for the angiogenic response to exercise training. This was tested in adult conditional, skeletal myofiber-specific VEGF gene-deleted mice (skmVEGF−/−), with VEGF levels reduced by >80%. After 8 wk of daily treadmill training, speed and endurance were unaltered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 49 publications
3
80
2
3
Order By: Relevance
“…In normal muscle, exercise provokes a strong angiogenic stimulus resulting in an increase in capillary density mediated by several growth factors including VEGF [29]. In the current study, despite using a rigorous exercise protocol for these experiments, neither demand ischemia nor sedentary ischemia proved to be a stimulus for increased VEGF expression (Figure 3A).…”
Section: Discussionmentioning
confidence: 63%
“…In normal muscle, exercise provokes a strong angiogenic stimulus resulting in an increase in capillary density mediated by several growth factors including VEGF [29]. In the current study, despite using a rigorous exercise protocol for these experiments, neither demand ischemia nor sedentary ischemia proved to be a stimulus for increased VEGF expression (Figure 3A).…”
Section: Discussionmentioning
confidence: 63%
“…VEGF is dominantly secreted by working skeletal muscles, an essential factor to increase capillary density, oxygen delivery and thereby exercise performance (109)(110)(111). Based on our previous results showing improved muscular exercise capacity after HIT (30), and now the finding of an increased VEGF response, we suggest that this mechanism is of high importance also in the HTx recipients.…”
Section: Hit and The Immediate Responses In Markers Of Inflammation Amentioning
confidence: 76%
“…Our laboratory has previously shown that life-long myofiber VEGF gene deletion in mice, simultaneously in both cardiac and skeletal myofibers (using Mck-Cre/VEGFLoxP cross-breeding), results in decreased cardiac and skeletal muscle capillarity, body weight and exercise capacity (Olfert et al, 2009). Moreover, we recently found that conditional, myofiberspecific VEGF deletion in skeletal muscles, achieved via a tamoxifen-inducible strategy initiated in adult mice, showed a modest (30%) effect on exercise capacity, but no effect on muscle capillarity in untrained mice (Delavar et al, 2014). However, the consequence of cardiac-specific VEGF gene deletion for exercise capacity was not evaluated in this study.…”
mentioning
confidence: 77%
“…Skeletal muscle makes up a large percentage of overall body composition. More recent studies from our laboratory conditionally targeted VEGF gene deletion only in mature myofibers of adult mice and showed that capillary number is not reduced in the soleus, gastrocnemius, plantaris and EDL (Delavar et al, 2014). Our laboratory has previously reported that localized deletion of the VEGF gene in locomotor skeletal muscle, using an AAV vector to deliver cre recombinase to VEGFLoxP mice, results in substantial capillary regression in adult mice (Tang et al, 2004).…”
Section: Postnatal Versus Embryonic Skeletal Myofiber Targeted Vegf Gmentioning
confidence: 97%